Update on Postsurgical Scar Management - Commander, Sarah Jane; Chamata, Edward; Cox, Joshua; Dickey, Ryan M.; Lee, Edward I. (Seminars in Plastic Surgery, 2016)
Postoperative scar appearance is often a significant concern among patients, with many seeking advice from their surgeons regarding scar minimization. Numerous products are available that claim to decrease postoperative scar formation and improve wound healing. These products attempt to create an ideal environment for wound healing by targeting the three phases of wound healing: inflammation, proliferation, and remodeling. With that said, preoperative interventions, such as lifestyle modifications and optimization of medical comorbidities, and intraoperative interventions, such as adherence to meticulous operative techniques, are equally important for ideal scarring. In this article, the authors review the available options in postoperative scar management, addressing the benefits of multimodal perioperative intervention. Although numerous treatments exist, no single modality has been proven superior over others. Therefore, each patient should receive a personalized treatment regimen to optimize scar management.
Keywords: scar management; scar revision; wound healing